Estudo de interações de parasitoides de insetos endófagos em frutos do cerrado - Nascimento, André Rangel (2010)
Interactions between endofagous insects in fruits play an important role in ecological communities, since the seed survivorship and hence the successes in recruitment of plant populations are directed related to damage caused by the herbivory from these insects. Because of the specialization of the herbivorous insects, the insect-plant interactions tend to be structured in compartments of insects which use different groups of plant. The aims of this study were: (1) to identify if insect-plant interactions in fruits of the cerrado are compartmented; and (2) to identify if plant species in compartments are related. With two monthly field trips, the fruits of 34 plant species were sampled. The insects that emerged from fruits were classified in morphospecies. A correspondence analysis was used to identify the compartments. About 97 morphospecies of insects were identified. Although there is no consensus if the competitive forces structure the compartmented networks or, if directly or indirectly, chemicals defences of plants, the compartmentation seems to be an overall characteristic of food webs and, thus, of insect-plant networks. There is also evidence of the role of the phylogeny in the structure of compartmented networks.